Hepatoprotective cocrystals of isoniazid: synthesis, solid state characterization, and hepatotoxicity studies - Yadav, Balvant; Gunnam, Anilkumar; Thipparaboina, Rajesh; Nangia, Ashwini K.; Shastri, Nalini R. (Crystal Growth & Design, 2019)
Isoniazid (INH) is one of the first line drugs used in combination with pyrazinamide and rifampicin for the management of tuberculosis. Idiosyncratic hepatotoxicity is one of the most common side effects of antitubercular therapy worldwide. The current study explores solid phase modification of INH by cocrystallization with various hepatoprotective coformers, namely chrysin, hesperetin, silibinin, syringic acid (SYRA), and quercetin (QUE) to address hepatotoxicity concerns. Cocrystals were obtained with SYRA and QUE. Supramolecular synthons based on pyridine-carboxyl and pyridine-hydroxyl synthon enabled the formation of cocrystals. INHSYRA and INHQUE cocrystals were characterized by FT-IR, DSC, and PXRD. Single crystal X-ray analysis of INHSYRA revealed that it crystallized in triclinic system with the P (1) over bar space group. Intrinsic dissolution rate studies (IDR) showed slow drug release from both the cocrystals. Hepatoprotective effects of INHSYRA and INHQUE cocrystals were evaluated by a single toxic dose study and a subchronic study for 28 days. Results from the subchronic study indicated significant increase in ALT, AST, and ALP enzyme levels in the INH-treated group whereas the enzyme levels in INHSYRA and INHQUE cocrystal treated group were comparable to that of the untreated group. This study demonstrates the in vivo hepatoprotective effects of coformers SYRA and QUE provide promising evidence for utility of nutraceutical based coformers, to tackle hepatotoxicity associated with various drugs.